Ironhand [compact disc, unabridged] - Fletcher, Charlie, 1960- (Fletcher, Charlie, 1960- Stoneheart trilogy, 2008)
Having upset the balance between the warring statues of London, twelve-year-old George is confronted with new challenges as he tries to free his captured friends Edie and the Gunner from the formidable Walker and deal with the three strange veins of marble, bronze, and stone that have begun to grow out of his hand.